Validation of a latent class analysis model for predicting mortality - Witzke, Donald B.; Castro, Luis; Dignman, Harvey F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An equation to predict mortality in institutions has been developed by Miller. Sabagh, and Dingman (1962). This equation was cross validated on a population of mentally ill in a state hospital in another state. The equation provided successful predictions of mortality (p < .0001) even though the weights had been derived for a younger and more severely handicapped group. It was concluded that a better understanding and better predictions would follow if the analysis had been based on the mentally ill population.